MANAJEMEN KEUANGAN SISA HASIL USAHA SEBELUM DAN SESUDAH PEMAKAIAN KPE (KARTU PEGAWAI NEGERI SIPIL ELEKTRONIK) - EFA WAHYU PRASTYANINGTYAS (STIE Indonesia Malang, 2017)
This research is a descriptive study using equalitative approach. Data were collected usinginterviews, observation and documentations. The results of this study indicate that financialmanagement is applied differently. Before applied KPE namely: special savings members isnot limited, members loans made easier because the pay system is still manual,facilitatingsebrak postal cooperative services to members if the current installment or need a loan at anytime. When applied KPE namely: special savings normalized to Rp 35.000,00, memberloan amountis limited by the criteria of remaining balance in KPE, sebrak postal servicesabolished.Keywords: Finacial management, result operation residual, KPE, cooperatives